Literasi Digital Pada Masyarakat: Etis Bermedia Sosial, Aman dan Nyaman - Sidiq, Purnomo (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2024)
The use of social media in society is a common thing nowadays, regardless of profession, position, rich or poor, but social media has become a supplement in daily activities, with the development of information and communication technology (ICT) in people's lives today, making society now unable to resist, let alone avoid, its development and of course positive and negative problems will arise and create awareness for society, so there is a need for education and strengthening understanding of literacy for the public so they don't get trapped in cyberspace, therefore it is very important to understand literacy. Digital in Society: Ethical, Safe and Comfortable Use of Social Media. The aim of the service is oriented towards understanding digital literacy activities among the community, so that these activities provide education to the community regarding the importance of understanding digital literacy in the ethical use of social media and the impact of using social media in life in today's digital era with efforts to strengthen and educate digital literacy and raising awareness about good understanding of Netiquette, with activity stages from preparation, survey, determination, activities and reporting providing steps and efforts in organizing Digital Literacy assistance activities in community life in general with an ethical or netiquette orientation towards the community in the use of digital media.